Dynamic Evolution Control for Fuel Cell DC-DC Converter - Ahmad Saudi Samosir; Tole Sutikno; Abdul Halim Mohd Yatim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Fuel cells are new alternative energy resource that has a great promise for distributed generation and electric vehicle application. However, fuel cells have a slow response due to their slow internal electromechanical and thermodynamic response. To optimize the fuel cell system performance, a fuel cell DC-DC converter with an appropriate controller which can regulate the power flow and automatically adjust the converter output voltage is needed. This paper proposes a new control technique for fuel cell DC-DC power converter. Design of the proposed control method for fuel cell DC-DC power converter is provided. A new approach for converter controllers synthesis based on dynamic evolution control theory is presented. In this paper, synthesis example of boost DC-DC converter is discussed. Performance of the proposed dynamic evolution control under step load variation condition is simulated under Matlab-Simulink environment. Simulation results show that the proposed techniques are capable for controlling fuel cell DC-DC converter.